(2E)-1-[2-Hydroxy-4-(2-methylpropoxy)phenyl]-3-(4-methylphenyl)prop-2- en-1-one - Maheta, J.G.; Barot, V.M.; Jotani, M.M.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The benzene rings in the title compound, C(20)H(22)O(3), form a dihedral angle of 10.39 (8)degrees. Overall, the molecule is approximately planar with the exception of one of the terminal methyl groups; excluding this group, the r.m.s. deviation for the remaining 22 non-H atoms is 0.0968 angstrom. The conformation about the C=C bond is E, and an intramolecular O-H center dot center dot center dot O hydrogen bond leads to the formation of an S(6) motif. In the crystal, linear supra-molecular chains are formed along the a axis via C-H center dot center dot center dot O contacts, and these are connected into double chains via C-H center dot center dot center dot pi interactions.